Pelatihan Public Speaking untuk Meningkatkan Kepercayaan Diri Siswa/I SMK Utama Tangerang Selatan - Fatimatuzahrotul Aini; Ikrimatul Amal (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2026)
The digital era and industrial competition require vocational high school (SMK) graduates to possess strong communication skills, particularly public speaking. Many students still face obstacles such as low self-confidence, glossophobia (fear of public speaking), and limited practical communication experience, so their ability to present ideas in academic settings and job preparation remains suboptimal. This community service program aims to strengthen public speaking skills of SMK Utama students especially XI through an integrated training that addresses psychological, technical, and practical aspects. The approach is grounded in experiential learning, combining lectures, simulations, hands-on practice, and constructive feedback. Implementation proceeds in stages: mental reconstruction (self-acceptance and positive affirmations), enhancement of verbal and nonverbal communication skills, and practice based on a growth mindset. Expected outcomes include increased self-efficacy, reduced public-speaking anxiety, and improved ability to deliver messages in a more structured, persuasive, and confident manner. Additionally, the program seeks to establish a school public-speaking community to foster a supportive, sustainable learning environment, thereby better equipping students with adaptive communication skills essential for entering the workforce and continuing education.